EKSISTENSI DAN OPTIMALISASI BADAN USAHA MILIK DESA (BUMDes) BERBASIS SYAR’I MENUJU DESA SEJAHTERA MANDIRI - Moh. Subhan (STIE Bakti Bangsa Pamekasan, 2020)
The development of several villages in Indonesia in the last decade has shown extraordinary developments. The village, which has been synonymous with backwardness and poverty, is slowly but surely starting to rise and develop. This is indicated by the decline in the category of very underdeveloped villages or underdeveloped villages to become developing, advanced and independent villages. The village is expected to become independent socially, culturally, economically and politically. Village independence is a condition in which the village has the ability to carry out development in all sectors to improve the quality of life and as much as possible for the welfare of the village community. Village independence is evidenced by the village's ability to meet its own needs and is not solely dependent on subsidies from the government, even though the village receives government assistance but only as a stimulant. One of the ways to encourage development at the village level is by giving the village government authority to independently manage the village scope through economic institutions at the village level. One of them is by developing and optimally managing Village-Owned Enterprises (BUMDes) in syar'i, through Islamic economic-based contracts. If the syar'i-based BUMDes is able to work well, especially being able to increase village original income and reduce unemployment, then in the future the village will be more prosperous and independent.